The castaways : a novel - Hilderbrand, Elin. (New York : Little, Brown and Co., 2009)
A Nantucket couple drowns, raising questions and precipitating conflicts among their group of friends.
Keywords: Quakers -- Fiction; Family secrets -- Fiction; Nantucket Island (Mass.) -- Fiction; Psychological fiction